Human umbilical cord mesenchymal stem cells inhibit coronary artery injury in mice with Lactobacillus casei wall extract-induced kawasaki disease - Guo, Hua; Jiao, Fuyong; Zhang, Xiaoyong; Feng, Yangmeng; Liu, Yang; Liang, Daoyan; Yan, Xiaohua; Zhang, Haixiang (Penerbit Universiti Kebangsaan Malaysia, 2022)
Kawasaki disease (KD) is a serious threat to children’s physical and mental health. This study investigated the effect of human umbilical cord mesenchymal stem cells (hUC-MSCs) on KD coronary arteritis induced by Lactobacillus casei wall extract (LCWE) in an animal model. Sixty BALB/C mice were randomly assigned to three groups (n = 20 mice per group). Mice in the model and stem-cell groups were injected with LCWE, while the control-group mice were injected with phosphate-buffered saline (PBS) for 2 days. At day 16 of modeling, PBS was injected into the control and model-group mice, and hUC-MSCs were injected into the stem-cell group mice for 10 days. At days 4, 15, 26, and 32 of modeling, echocardiography and histopathology were performed to examine the cardiac structure and the morphological changes in the coronary arteries in each group. B-ultrasonography showed that 57.5% (23/40) of the mice had coronary artery lesions, of which 5% (2/40) had right coronary artery aneurysm, 27.5% (11/40) had coronary artery wall thickening, a widened inner diameter of the main artery of the left coronary artery, and thickened intima. Histopathology showed slight swelling of the epicardium of the aortic valve, mitral valve, right ventricle, and atrium, as well as scattered infiltration of a few neutrophils. Following hUC-MSCs intervention treatment, B-ultrasonography showed a decrease in the main coronary artery diameter, while histopathology showed no obvious vascular inflammatory reaction or other obvious abnormalities. These findings highlight that hUC-MSCs inhibit coronary artery injury in animal models of KD induced by LCWE.